Penyiram Tanaman Otomatis Menggunakan Soil Moisture Berbasis Arduino Uno - Dimas Bayu Anggoro; Anggun Permata Sari; Viona Sharaswati; Okta Putpita Sari; Aji Muamar (SEMINAR NASIONAL TEKNOLOGI INFORMASI & KOMUNIKASI, 2021)
Pandemic in today, often we feel bored with just at home all day. Not infrequently we try new things to fill your free time. Planting into one of the activities that can be done at home. It does not have to be done in a large place, planting can be done in the home page. The problem of plant sprinklers cannot always be controlled manually in their watering, because decorative plants need different water content so that if too much water or too little water can affect plants. The development of technology is so rapid without us realizing it. More and more tools are made with the aim of being able to facilitate human work. One of them is by making plant sprinklers automatically. With this tool, it is expected that we no longer need to bother to water plants repeatedly. This tool will know when watering must be done, so that the watering of the plant can be more efficient at the time and the right conditions. This tool uses Arduino Uno as a tool control center and soil moisture to measure soil moisture. The system will be in a program ins such a way that in the condition of the moisture of a certain soil water pump engine will live and die automatically.